EKSPLORASI PENDEKATAN PEMBELAJARAN BERPUSAT PADA SISWA DALAM PEMBELAJARAN JARAK JAUH: PELUANG DAN TANTANGAN - Syafi'i, Muhammad Imam (Prodi PGMI IAI Darul Ulum Kandangan, 2024)
Distance learning has become a major alternative in education, especially when physical access to schools is limited. In this context, the exploration of effective learning models, especially student-centered ones, becomes crucial to study. The objective of the study is to explore the concept of student-centered attachment, student-centric learning approaches, as well as opportunities and challenges in distance learning. The method used is a library research method. The results show that the concept of a student-centric learning approach is an approach that places students as active subjects in the learning process. Meanwhile, the exploration of the approach is carried out through increased student involvement, improved understanding of concepts, increased academic achievement, and optimizing the role of teachers. The challenges include difficulties in student involvement, a lack of infrastructure and access, difficulty understanding individual needs, and limited resources and training. Finally, the opportunity, where the opportunity can be to personalize learning, use technology, develop skills, and partner with parents and the community, Hopefully, this study will provide a deeper understanding of how this approach can be applied effectively in the context of distance learning.